2019
DOI: 10.1021/acs.iecr.8b06057
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Tailoring Bubble Morphology in Microchannel by Nanoparticles Self-assembly

Abstract: Precisely tailoring bubble morphology is always a long-standing great challenge. In this work, a facile and scalable method to generate nonspherical bubbles with long-term stability is proposed. Taking advantage of the electrostatic interaction between silica nanoparticles (SNPs) and cationic surfactants, the SNPs are decorated with surfactants and endowed with interfacial activity. Due to the rearrangement of surfactants, the decorated SNPs transform to a kind of Janus particles at the gas−liquid interface. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The relatively low resistance of silica nanofluids to temperature and salt aggravates the aggregation and precipitation after long-time use, which probably gives rise to the blockage of the pore-throats structure underground causing formation pollution (Das 2009). To overcome this problem, methods for preparing uniform and stable nanofluids are constantly developed (Li et al 2011;Babita and Gupta 2016), including physical and chemical modification methods (Esfandyari et al 2014;Arulprakasajothi et al 2015;Wu et al 2019). Tushar et al prepared nanofluids by adding polymers (Arulprakasajothi et al 2015) and proved that polymer can enhance nanofluids stability.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low resistance of silica nanofluids to temperature and salt aggravates the aggregation and precipitation after long-time use, which probably gives rise to the blockage of the pore-throats structure underground causing formation pollution (Das 2009). To overcome this problem, methods for preparing uniform and stable nanofluids are constantly developed (Li et al 2011;Babita and Gupta 2016), including physical and chemical modification methods (Esfandyari et al 2014;Arulprakasajothi et al 2015;Wu et al 2019). Tushar et al prepared nanofluids by adding polymers (Arulprakasajothi et al 2015) and proved that polymer can enhance nanofluids stability.…”
Section: Introductionmentioning
confidence: 99%
“…Stolovicki et al 10 found that the uniformity of the droplet's size deteriorated with the increase of the flow rate of the dispersed phase. Mittal et al 9 found that the coalescence between droplets is the key factor affecting the uniformity of droplets’ volume 13 …”
Section: Introductionmentioning
confidence: 99%
“…Recent development of microfluidic devices allows the study of flow behaviors of viscoelastic fluids in micro pore unit directly 27‐31 . Researchers are able to analyze quantitatively the velocity fields of viscoelastic fluids, 32 migration of crude oil droplet, 33 and interface merging or breakup of bubble 34 .…”
Section: Introductionmentioning
confidence: 99%